Morphofunctional characteristics of the rat's bladders during first month of life. - Khytryk, A. Y. (Морфологія / Morphologia / Morfologìâ, 2019)
Background. One of actual problems in medical practice are diseases of the urinary system and the bladder in particular (20%). Many diseases of the urinary system in older children and adults occur in the neonatal period or even before birth. Objective.The aim of this study was to study the morphological features of the bladder of rats in the period of early postnatal ontogenesis.Methods. Study consisted of a histological examination of the bladders of 24 rats and the mathematical processing of data. The containment and manipulations on animals were in accordance with the “General ethical principles of experiments on animals.” A morphometric study and photomicrography were performed using a ZEIZZ microscope with an Axiocam 105 color digital microplotter. Variation statistical methods were used to using perform a quantitative analysis of the results of a morphometric study by using programs such as Excel and STATISTICA. Results. Next properties were studied: the average length and thickness of the folds of the mucous membrane, the thickness of the urothelia and its own plate, muscle shell and outer shell. The average number of lymphocyte cells in the field of view. An increase in the thickness of the membranes of the bladder was observed, with a maximum thickness being reached by the 30th day of life. Also, by the end of the first month, an increase in the quantitative and qualitative composition of cells of the immunomorphological complex in the mucous structure is well pronounced. This can be attributed to a change in the type of nutrition of the rats, since from 14 to 21 days there is a transition from dairy to natural nutrition.